A study on the relationship between the music themes and the motion picture: the lord of the rings trilogy / Rozaimi Rosli - Rosli, Rozaimi (2009)
For something we often barely notice: film music is in fact highly persuasive and effective. It creates tension, generates an emotional journey, and it is undoubtedly one of the most important aspects of true cinematic experience. Upon closer inspection, it can be realized that film music is a highly complex genre and a genuine work of art not only it is capable to trigger an immediate emotional impact, but, it has also succeeded in giving birth to some of the most outstanding music that has ever been created in the twentieth century until in the present day. Film music is usually fragmentary and relies extensively on an understanding that it is not solely an organic part of the music, but rather; as a negotiation between the logic of the film and the logic of the music. l There is an ongoing debate amongs scholars pertaining to music's ability to convey meaning. Over the past decades, theorists and historians have explored music's ability to act as a narrator, to tell stories, and to convey emotions, represent characters, or allude to their actions? Amongs these scholars, there are those who believe that music alone is capable to narrate; others believe that the composer is narrating through music; while some believe the listeners hear the music as though it is narrating regardless of the composer's intent; and those who believe that music cannot narrate due to its inherent lack of a narrator.3 Film scores in particular; provide an analyst with literal objects and stories to which the music's meaning can be compared to. At the very least, a film score's role is to accompany the events occurring on-screen - which in tum suggests the music's ability to reflect some sort of meaning to the audience. However, it is possible that film music may do even more than simply accompanying the visual aspects of the movies; that it is also capable of provoking and enhancing the emotional experience of the audience, and additionally providing them with vital information pertinent to the story line and character development.